Mastering the Old Testament ; v. 16A - McKenna, David Loren (Dallas, TX Word, 1994)
Contents : v. 16A : Isaiah 1-39 Includes bibliographical references.
Keywords: Bible. O.T. Isaiah I-XXIX -- commentaries